Malawi Economic Monitor, June 2019 : Charting a New Course - World Bank (World Bank, Lilongwe, Malawi, 2019)
The Malawi Economic Monitor (MEM) provides an analysis of economic and structural development issues in Malawi. This edition was published in June 2019. It follows eight previous editions of the MEM and is part of an ongoing series, with future editions to follow twice each year. The aim of the publication is to foster better-informed policy analysis and debate regarding the key challenges that Malawi faces in its endeavor to achieve high rates of stable, inclusive and sustainable economic growth. The MEM consists of two parts: Part 1 presents a review of recent economic developments and a macroeconomic outlook and risks. Part 2 focuses on a special topic relevant to Malawi’s development prospects.